New one way hash algorithm using non-invertible matrix - Abutaha, Mohammed; Hamamreh, Rushdi (IEEE, 2013)
Hash functions are widely used in encryption schemes and security layers of communication protocols for data integrity, digital signature and message authentication codes [18]. Hash function is a well-defined procedure that converts a large data into a small one, The returned value from hash function is called hash code, It is well known that Hash algorithm works in one way and cannot be reversed, In this paper, The new one way hash algorithm will be designed by using two steps. Firstly, we will convert the input data into matrix system by using all necessary conversions to generate the initial hash value. Secondly, use the output of the first step to make a digest for these data and finally generate the secure hash value.